2022
DOI: 10.15835/nbha50312915
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the functional role of tea microbes on tea growth, quality and resistance against pests and diseases

Abstract: Tea is an economical and most widely used beverage across the globe owing to its unique fragrance and flavor. Plant microbe interaction has emerged as an important topic which got the attention of scientists to improve plant performance. Tea microbes remained a prominent research topic for scientists over the years as tea microbes helps in nutrient cycling and stress management which in turn improve the tea growth, yield and quality. The roots of tea plants are colonized by various microbes including arbuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Guo et al have suggested that long-term tea cultivation results in the accumulation of acidic compounds in the rhizosphere soil, leading to soil acidification, nutrient depletion, and a significant decrease in soil aggregate stability [16]. Additionally, the accumulation of secondary metabolites and above-ground litter in tea trees is able to cause autotoxicity, which inhibits tea tree growth [17,18]. In addition to rhizosphere soil, the microecological conditions of the surrounding soil also have a profound impact on the productivity of the plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al have suggested that long-term tea cultivation results in the accumulation of acidic compounds in the rhizosphere soil, leading to soil acidification, nutrient depletion, and a significant decrease in soil aggregate stability [16]. Additionally, the accumulation of secondary metabolites and above-ground litter in tea trees is able to cause autotoxicity, which inhibits tea tree growth [17,18]. In addition to rhizosphere soil, the microecological conditions of the surrounding soil also have a profound impact on the productivity of the plantations.…”
Section: Introductionmentioning
confidence: 99%